Analysis of the albumin‐bilirubin score as an indicator of improved liver function among hepatitis C virus patients with sustained viral response after direct‐acting antiviral therapy. Issue 7 (16th June 2022) - Martínez Herreros, Ángela; Sangro, Bruno; García Rodriguez, Alba; Pérez Grijalba, Virginia
Abstract: Background and Aim: To investigate the performance of the albumin‐bilirubin (ALBI) score as an indicator of improved hepatic function using a cohort of hepatitis C virus (HCV) patients with sustained viral response (SVR) after direct‐acting antiviral therapy (DAA). Methods: HCV patients who achieved SVR after DAAs between 2015 and 2016 were followed for at least 24 months. Changes in ALBI were evaluated in the entire cohort and according to liver function and liver stiffness status at baseline. Results: Four hundred ninety‐seven patients were enrolled. Exactly 96.92% were in Child–Pugh (CTP) class A, and 42% had grade 2 fibrosis. Median ALBI was −3.02, while 87.7 and 11.3% of patients were in ALBI grades 1 and 2, respectively. ALBI improved significantly over time, particularly in patients who had a worse ALBI at baseline. Exactly 77% of patients initially in ALBI grade 1 and 93.9% of those in ALBI grades 2–3 improved their ALBI score in different amounts. Improved ALBI was observed irrespective of CTP score at baseline. Median ALBI at baseline and after 24 months were −3.03 and −3.27 for CTP 5, 2.02 and −2.88 for CTP 6, and −1.59 and −2.84 for CTP >6. Similarly, a significant improvement in ALBI was observed within each stage of fibrosis at baseline. Conclusion: ALBI was a good indicator of improved hepatic function in HCV patients with SVR after DAA therapy, able to identify changes even in those patients who started DAA therapy with well‐preserved function and mild fibrosis. This simple, objective, and noninvasive test should be evaluated in other clinical scenarios where liver function is relevant. Abstract : A cohort of 497 patients with chronic hepatitis C (97% in Child–Pugh (CTP) class A and 53% with fibrosis grades 0–2) who achieved sustained virological response after direct antiviral therapy were followed for at least 24 months; albumin‐bilirubin (ALBI) score improved significantly over time, including patients with ALBI grade 1 or CTP A5 at baseline. A significant improvement in ALBI was also observed across stages of fibrosis at baseline.